Perancangan dan Analisis Kinerja Aplikasi Pembelajaran Praktik Geomatika Berbasis Android - Totok Sulistyo; Wahyu Anhar; Karmila Achmad (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Many researchers study the implementation of smartphone applications (apps[WU1] ) for education, inplementation of smartphone apps for geomatic education have advantages such as independent experiences can be acquired by user at anytime and anywhere. The aims of this research are designing, developing and analysis the application of GeomatikaDroid bugs, crash and ANR so that its performance can be improved. The methods that were carried out in this research consisted of desk study, collecting requirement of users candidate, analysis and formulation user requirement, designing application, implementation, testing, Application publication, maintenance and improment of application performance. Result of this research is the application of Android (GeomatikaDroid) which is giving aids to user in topograpic measurement. Application of GeomatikaDroid can be developed using Java Programming in client side and PHP in server side and MySQL as database server. GeomatikaDroid has function in reading, recording, calculating and storing data of both of analog and digital teodholit measurement. The performance was increased started from version 1.1 to version 1.10, proven by declining crash and ANR or improving stability, rising download rate and the average of star rate is 4.944 out of 5.